2021
DOI: 10.1111/1365-2664.13875
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of small barriers on river‐resident fish

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 87 publications
2
27
2
2
Order By: Relevance
“…Across all 72 fish that attempted passage, shelter departure latency was retained in the best candidate passage success model for all fish, suggesting that bolder individuals (i.e., those that left the shelter quicker) had a greater probability of succeeding in passage than shyer fish. This supports the predictions of Hirsch et al (2017) and findings of Jones et al (2021), but contrasts with the findings reported by Landsman et al (2017) who showed no relationship between boldness and passage success. However, when reducing the sample size to only those that had left the shelter and thus included in the PCA to obtain behavioral trait dimensions, then Boldness btd was not retained by any candidate passage success model.…”
Section: F I G U R Esupporting
confidence: 75%
See 3 more Smart Citations
“…Across all 72 fish that attempted passage, shelter departure latency was retained in the best candidate passage success model for all fish, suggesting that bolder individuals (i.e., those that left the shelter quicker) had a greater probability of succeeding in passage than shyer fish. This supports the predictions of Hirsch et al (2017) and findings of Jones et al (2021), but contrasts with the findings reported by Landsman et al (2017) who showed no relationship between boldness and passage success. However, when reducing the sample size to only those that had left the shelter and thus included in the PCA to obtain behavioral trait dimensions, then Boldness btd was not retained by any candidate passage success model.…”
Section: F I G U R Esupporting
confidence: 75%
“…( 2017 ) and findings of Jones et al. ( 2021 ), but contrasts with the findings reported by Landsman et al. ( 2017 ) who showed no relationship between boldness and passage success.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This may involve making people more aware of the impacts of salmonid invasions and passing more stringent legislation. Exclusion barriers could also be deployed around galaxiid refugia to reduce the risk of salmonid invasions (Jones et al 2021b), but care must be taken to ensure this does not impact on native galaxiids, which may pose a challenge as even small barriers can have negative impacts on weak swimmers (Jones et al 2021a). Brown trout is subject to a bag limit and a strict fishing season and it might be useful to consider lifting these restrictions in some places to slow down the invasion front.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%